Exploring the use of social constructivist methodologies in teacher practice and student engagement in chemistry. - NUGENT, SINÉAD (Trinity College Dublin. School of Education. Discipline of Education, 2019)
This thesis comprises a self-study action research inquiry into the practice of a post-primary chemistry teacher in Ireland. The research had a collaborative aspect to it, as a number of students were invited to participate through cogenerative dialogue. This research was enacted as a methodology to improve chemistry learning and teaching in the class and to address difficulties in engaging students to become active learners. My style of teaching was traditional, mostly didactic, with very little social interaction between the students during lessons. The emphasis was on the importance of the summative Leaving Certificate exam, as is current practice in most Irish schools. I endeavoured to create a more engaging and active form of pedagogy. Methods undertaken in this research included; a critically reflective approach, research and implementation of social constructivist methodologies into teaching and co-generative dialogues with students. This was all enacted through an action research approach, combined with social constructivist values and a deep consideration of ethical and moral implications of the research. The data-collection took place over the academic year 2016-2017 with a 5th year chemistry class. The data collected comprised of; social constructivist designed lesson plans, field notes on lessons, artefacts of student work, a teacher reflective diary and transcripts of co-generative dialogue discussions with the students. From engagement with the research I gradually reconceptualised my identity as a reflective and critical thinker through critical reflections on my practice and research into social constructivist methodologies. I also began to challenge entrenched cultural norms and enact changes in the purpose of improving practice. This research impacted my teaching practice and developed an engaging pedagogy that resulted in the students becoming active in their own learning. From this study, social constructivist methodologies can develop and support teachers in their understanding of the nature of science, promoting teaching towards more social approaches. Social constructivist methodologies could be developed into a pedagogical approach that could engage students in the subject of chemistry and support them in becoming active learners. There is also potential for the social constructivist methodology to be implemented into curriculum, when supported by on-going professional development for teachers, and acknowledgement of influencing cultural factors, on its implementation in Ireland.
APPROVED
Keywords: Cogenerative Dialogue; Science Education; Social Constructivism; Teacher Reflection; Student-Teacher relationships